2019
DOI: 10.1186/s12872-019-1217-x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and risk factors of patients with types of acute coronary syndrome presenting to a tertiary care hospital in Sri Lanka

Abstract: BackgroundAcute Coronary Syndrome (ACS) is one of the leading causes of death worldwide and studies have shown higher mortality rates and premature death in South Asian countries. The occurrence and effect of risk factors differ by type ofACS.Epidemiological studies in the Sri Lankan population are limited.MethodsThis is a cross sectional descriptive study conducted at the Teaching Hospital Peradeniya, Sri Lanka among patients presenting with ACS. Data was collected by an interviewer administered structured qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
37
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 27 publications
7
37
0
8
Order By: Relevance
“…Another significant association was found between HTN and occurrence of NSTEMI. This is supported by findings of Udaya Ralapanawa et [10] who also found higher rates HTN in Significant association was found between smoking and occurrence of STEMI and significant association was found between Hypertension and occurrence of NSTEMI.…”
Section: N (Nstemi)supporting
confidence: 82%
See 4 more Smart Citations
“…Another significant association was found between HTN and occurrence of NSTEMI. This is supported by findings of Udaya Ralapanawa et [10] who also found higher rates HTN in Significant association was found between smoking and occurrence of STEMI and significant association was found between Hypertension and occurrence of NSTEMI.…”
Section: N (Nstemi)supporting
confidence: 82%
“…analysis of the risk factors with outcomes of ACS our study observed significant association of smoking with STEMI. The findings [10] support this observation where they also found significant association between smoking and STEMI. Another significant association was found between HTN and occurrence of NSTEMI.…”
Section: N (Nstemi)supporting
confidence: 78%
See 3 more Smart Citations